Uses of Social Security Allowances on Socio-Economic Status of People in Kaski - Ranabhat, Deepesh; Adhikari, Sujita (Journal of Business and Management, 2022)
Background: Social security allowance refers to benefit given by the government as a way of helping low-income individuals of society such as the sick, the jobless, the retired, the disabled, the widowed, the single-parent families, etc. Objectives: This study aims to look at the change in the socio-economic well-being of people because of Social Security Allowances and find out the factors related to socio-economic level. Methods: This study has purposively taken 170 sample respondents from Rupa Gaunpalika and Pokhara Metropolis. Information has been collected using a structured questionnaire. Results: This study finds that social security allowances facilitate increasing the number of friends, getting involved in social activities, increasing their importance to peers and associates, feeling privileged that the government is looking after them, increasing their self-respect, getting respect from neighbors, reduce financial dependency, meet their regular household expenditure, purchase of health service and medicine and meet their clothing needs. Further, it reveals that area of living, sex, and educational status are the foremost factors associated with the socio-economic level of the beneficiaries. Conclusion: This study concludes that social security allowance plays an important role in the socio-economic well-being of the individuals and the government should increase the amount of allowances for living the normal life of the beneficiaries